Perspectives of youth in foster care on essential ingredients for promoting self-determination and successful transition to adult life: My life model. (February 2018) - Powers, Laurie E.; Fullerton, Ann; Schmidt, Jessica; Geenen, Sarah; Oberweiser-Kennedy, Molly; Dohn, JoAnn; Nelson, May; Iavanditti, Rosemary; Blakeslee, Jennifer; ,
Abstract: Research clearly documents the serious challenges and poor outcomes experienced by many young people exiting foster care, as well as compounded disparities for the high percentage of youth in care who are identified with disabilities and/or mental health challenges. However, very little research has been conducted to specify or validate effective models for improving the transition trajectories of youth exiting care. Evidence suggests the My Life self-determination enhancement model offers a promising approach for supporting youths' self-determined and positive transition to adulthood. The model includes youth-directed, experientially oriented coaching in the application of self-determination skills to achieve youth-identified transition goals, coupled with peer mentoring workshops that provide opportunities for learning, networking and fun. This in depth qualitative study of 10 youth who completed the My Life intervention focused on investigating coaching and mentoring elements and processes that youth participants identify as most important to their success, with the intention of informing the further development of youth-directed approaches to supporting young people who are transitioning to adulthood. Themes emerged around the centrality of youth self-direction, important processes in the coaching relationship, the essential value of experiential activities and self-determination skill development, and peer mentoring experiences that youth identified as fostering their success. Implications are discussed for research and practice in supporting youth exiting foster care. Highlights: My Life model fosters self-determination, achieving goals and managing challenges. Effective coaching and mentoring involves supporting youth on self-defined goals. Coaching supports relationship, activity engagement and self-determination skills. Mentoring based on shared life experience can promote knowledge and confidence. Improving transition outcomes necessitates listening to and learning from youth.